Ferroelectric and Magnetic Properties in Room‐Temperature Multiferroic GaxFe2−xO3 Epitaxial Thin Films. (27th November 2017) - Katayama, Tsukasa; Yasui, Shintaro; Hamasaki, Yosuke; Shiraishi, Takahisa; Akama, Akihiro; Kiguchi, Takenori; Itoh, Mitsuru
Abstract: GaFeO3 ‐type iron oxide is a promising room‐temperature multiferroic material due to its large magnetization. To expand its usability, controlling the ferroelectric and magnetic properties is crucial. In this study, high‐quality Ga x Fe2– x O3 ( x = 0–1) epitaxial films are fabricated and their properties are systematically investigated. All films exhibit room‐temperature out‐of‐plane ferroelectricity, showing that the coercive electric field ( E c ) decreases monotonically with x . Additionally, the films show in‐plane ferrimagnetism with a Curie temperature ( T C ) >350 K at x = 0–0.6. The coercive magnetic field ( H c ) decreases with x at x ≤ 0.6, but shows a constant value at x > 0.6, whereas the saturated magnetization ( M s ) increases with x at x ≤ 0.6, but decreases with x at x > 0.6. X‐ray magnetic circular dichroism reveals that the large magnetization at x = 0.6 is derived from Fe 3+ (3d 5 ) at octahedral sites. The controllable range of the E c, H c, and M s values at room temperature (400–800 kV cm −1, 1–8 kOe, and 0.2–0.6 µB /f.u.) is very wide and differs from those of well‐known multiferroic BiFeO3 . Furthermore, the Ga x Fe2− x O3 films exhibit room‐temperature magnetocapacitance effects, indicating that adjusting T C near room temperature is useful to achieve large room‐temperature magnetocapacitance behavior. Abstract : Ga x Fe2− x O3 films simultaneously exhibit room‐temperature out‐of‐plane ferroelectricity and in‐plane ferrimagnetism . The controllable range of the ferroelectric and ferrimagnetic parameters at room temperature is very wide and differs from those of well‐known multiferroic BiFeO3 . Furthermore, the films exhibit room‐temperature magnetocapacitance effects, indicating that adjusting T C near room temperature is useful to achieve large room‐temperature magnetocapacitance behavior.